Irreversible HER2 inhibitors overcome resistance to the RSL3 ferroptosis inducer in non-HER2 amplified luminal breast cancer - Park, Soon Young; Jeong, Kang Jin; Poire, Alfonso; Zhang, Dong; Tsang, Yiu Huen; Blucher, Aurora S.; Mills, Gordon B. (Cell death & disease, 2023)
Ferroptosis, a form of programed cell death, can be promoted by inhibitors of the xCT transporter (erastin) or GPX4 (RSL3). We found that GPX4, but not the xCT transporter, is selectively elevated in luminal breast cancer. Consistent with this observation, the majority of luminal breast cancer cell lines are exquisitely sensitive to RSL3 with limited sensitivity to erastin. In RSL3-resistant, but not sensitive, luminal breast cancer cell lines, RSL3 induces HER2 pathway activation. Irreversible HER2 inhibitors including neratinib reversed RSL3 resistance in constitutively RSL3-resistant cell lines. Combination treatment with RSL3 and neratinib increases ferroptosis through mitochondrial iron-dependent reactive oxygen species production and lipid peroxidation. RSL3 also activated replication stress and concomitant S phase and G2/M blockade leading to sensitivity to targeting the DNA damage checkpoint. Together, our data support the exploration of RSL3 combined with irreversible HER2 inhibitors in clinical trials.